SOME FUNDAMENTAL THEORIES OF CRITICAL DISCOURSE ANALYSIS - Fariza Azkiya Ali (Universitas Muhammadiyah Makassar, 2018)
This paper study explains about some fundamental theories of Critical Discourse Analysis such as focus on dominance relations by elite groups and institutions as they are being ordained and the overt sociopolitical stance of discourse analysis. Context social structure: Situations of discursive interaction are similarly part or constitutive of social structure; for example, a press conference may be a typical repetition of organizations and media institutions. That is, “local” and more “global” contexts are closely related, and both exercise constraints on discourse. Personal and social cognition: Language users as social actors have both personal and social cognition: personal memories, knowledge and opinions, as well as those shared with members of the group or culture as a whole. Both types of cognition inﬂuence interaction 006 and discourse of individual members, whereas shared “social representations” govern the collective actions of a group.